SYMBOLISM ON GERARD MANLEY HOPKINS POEMS: A SEMIOTICS APPROACH - ESTRINI , UPIT TRIE (2007)
This research paper observer symbolism on Gerard Manley Hopkins's Poems. The major aim in this study is to reveal the dominant symbol used in Gerard Manley Hopkins Poems using semiotic theory. Semiotic theory emphasizes the role of signs system in the construction of reality. This research is descriptive qualitative research. The researcher restricts Gerard Manley Hopkins Poems into its subject matter and analyzes the data to get the meaning behind the symbol. The poems that the writer analyzes in this research paper are Spring and Death, The Nightingale, The Sea and skylark, The Caged Skylark, The Lantern Out of Doors, The Grows Less, I Wake and Feel the Fell Dark, Not Day, To His Watch Looks How Spring Opens with Disabling Cold. The result shows that here the writer finds five symbol used by Gerard Manley Hopkins there are : 1) Symbol of things, 2) Symbol of situation, 3) Symbol of color, 4) Symbol of religion and symbol of sound. All of those symbols have related meaning with human life and his relation with God. The dominant symbol that used in Gerard Manley Hopkins Poem are symbol of thing and symbol situation.